Klasycyzm i metafizyka. (O wczesnej twórczości Jarosława Marka Rymkiewicza) - Woźniak-Łabieniec, Marzena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2001)
The present article is to recall the general principles of J. M. Rymkiewicz’s classicism and to stress those of his theses that roused a lot of controversies among critics (diagnosis of the culture crisis, time conception, theory of archetypes). Also it is essential to examine the poet’s way to express these theories in his poetry. The investigation helps us to find a contemporary poet interested in metaphysics. In his early poems he expressed various meanings of that branch of philosophy. The first expression is his theory of archetypes. By this he intends to touch the sphere of collective subconsciousness in order to evoke the forgotten archetypal models and to bring them back to life by means of symobls of the time being. His second theory can be described as “awakening the dead” . By poetry (arts) the present generation should get in touch with its ancestors to “wake them up” and thus to cause them to return to us. His third theory has been a continuation of baroque metaphysical poets’ expression. Their influence can be seen in his poems that remind us of Naborowski’s and the Morsztyns’ vocabulary and way of describing images. There are questions asked to the God about the sense of this life and eternity.